2006
DOI: 10.1152/jn.00955.2005
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Three-Dimensional Surface Slant in Cat Visual Areas 17 and 18

Abstract: Sanada, Takahisa M. and Izumi Ohzawa. Encoding of threedimensional surface slant in cat visual areas 17 and 18. J Neurophysiol 95: 2768 -2786, 2006. First published January 4, 2006 doi:10.1152/jn.00955.2005. How are surface orientations of threedimensional objects and scenes represented in the visual system? We have examined an idea that these surface orientations are encoded by neurons with a variety of tilts in their binocular receptive field (RF) structure. To examine whether neurons in the early visual ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 52 publications
9
43
2
Order By: Relevance
“…The binocular interaction profiles in the XL-XR domain are elongated along the diagonal, indicating that the neuron is sharply tuned for binocular disparity and its preferred disparity is constant for a relatively large range of X positions. Such inseparable interaction profiles were common in most complex cells we analyzed (26 of 34 complex cells; 7 of 28 simple cells), as expected from previous studies using 1D dichoptic stimuli (Ohzawa et al, 1990;Anzai et al, 1999b;Sanada and Ohzawa, 2006). The interaction strength map produced from the matrix of the XL-XR interaction maps exhibits an elliptic profile elongated along a diagonal (Fig.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The binocular interaction profiles in the XL-XR domain are elongated along the diagonal, indicating that the neuron is sharply tuned for binocular disparity and its preferred disparity is constant for a relatively large range of X positions. Such inseparable interaction profiles were common in most complex cells we analyzed (26 of 34 complex cells; 7 of 28 simple cells), as expected from previous studies using 1D dichoptic stimuli (Ohzawa et al, 1990;Anzai et al, 1999b;Sanada and Ohzawa, 2006). The interaction strength map produced from the matrix of the XL-XR interaction maps exhibits an elliptic profile elongated along a diagonal (Fig.…”
Section: Resultssupporting
confidence: 83%
“…The separable interaction profile was a characteristic of most simple cells we analyzed (21 of 28 simple cells, 7 of 34 complex cells). This is expected from previous studies where binocular interaction profiles were examined by using one-dimensional (1D) noise stimuli elongated along the Y-axes (Ohzawa et al, 1990;Anzai et al, 1999a;Sanada and Ohzawa, 2006). The strength of binocular interaction decreases isotropically in the matrix of the XL-XR maps with increasing distance from the center.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…As in an earlier study [30], some cells responded best when the SF presented to the two eyes was different. In these cells, Baba et al showed that the interocular difference in preferred SF was preserved across subunits.…”
Section: Extending the Energy Modelsupporting
confidence: 74%